Do firms in the Islamic index differ from others? Evidence of cost of debt in sharia firms in Indonesia - Vidia Gati; Iman Harymawan; Mohammad Nasih (Economies, 2022)
This study investigates the effect of sharia firms on the cost of debt in the Indonesian market. We use OLS regression to examine the relationship by applying 1870 data observations of nonfinancial companies registered on the Indonesia Sharia Stock Index (ISSI) during 2012-2018. We found that sharia firms are negatively related to the cost of debt, and sharia firms with a higher percentage of independent commissioners are not associated with the cost of debt. These findings indicate that a more significant number of independent commissioners sitting on the board will not stimulate a sharia firm's position to get a lower cost of debt. Furthermore, our results are robust after performing the endogeneity test. Based on this study, we suggest that independent commissioners who represent aspects of governance also need to be developed using firm characteristics as other moderating variables. Sharia firms are viewed by lenders as having corporate behaviors that are ethical and worthy to get low interest on the debt. Even though the financial structure of sharia firms has lower leverage than non-sharia firms, it does not mean that they are seen as closed firms.
Keywords: 330; cost of debt; independent commissioners; sharia firms